2016
DOI: 10.1088/2053-1583/3/3/034001
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-metallic nanocomposites as modifiers in electrochemical glucose biosensor transducers

Abstract: Graphene sheets and three different graphene-metallic nanocomposites including graphene-copper (graphene-Cu), graphene-nickel (graphene-Ni) and graphene-platinum (graphene-Pt) were prepared and characterized in the first place. Then the electrochemical performances of these nanocomposites were tested in glucose biosensor transducers, which were formed by combining these metallic nanocomposites with glucose oxidase enzyme and glassy carbon paste electrode (GCPE). This is the first work that includes the usage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Amongst the three graphene‐metallic nano‐composites, the graphene‐copper modified electrode exhibited the lowest detection limit of 2.87 μM between the linear range 25–400 μM. Graphene‐nickel had the highest detection limit of 24.71 μM in the linear range of 250−600 μM …”
Section: Sensors and Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amongst the three graphene‐metallic nano‐composites, the graphene‐copper modified electrode exhibited the lowest detection limit of 2.87 μM between the linear range 25–400 μM. Graphene‐nickel had the highest detection limit of 24.71 μM in the linear range of 250−600 μM …”
Section: Sensors and Biosensorsmentioning
confidence: 99%
“…Graphene-nickel had the highest detection limit of 24.71 μM in the linear range of 250 À 600 μM. [128] Further, in recent years the application of graphene as a glucose biosensor has progressed significantly. Shanbhag and Prasad [129] proposed the fabrication of graphene oxide and reduced graphene oxide as a glucose sensor, and successfully applied it for monitoring glucose concentration in saliva.…”
Section: Electrochemical Enzymatic Biosensors For Glucose Detectionmentioning
confidence: 99%
“…Altuntas et al . prepared three graphene materials with metallic nanostructures: graphene‐Ni, graphene‐Cu, and graphene‐Pt, which were used to immobilize GOD on glassy carbon paste electrodes. Using amperometry they observed that these hybrid composites promote electrocatalysis of glucose oxidation at +0.90 V ( νs .…”
Section: Graphene Used In Enzymatic Biosensingmentioning
confidence: 99%
“…Here, the first step of graphene oxide synthesis is very important for graphene to exhibit the desired properties (conductivity, mechanical, etc.) [13][14][15]. 106…”
mentioning
confidence: 99%